Animkee - Schlonies, James

(untitled) - Sanchez-Pimienta, Carlos; Masuda, Jeffrey (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2019)
In my video, I (James Schlonies) tell the story of how I struggled when I was younger. I went through all mental health services available in my town, but sometimes I just felt worse after. When I was in grade 7, I started going to M’Wikwedong. My family and I received help from M’Wikwedong to cope with what I was going through. Drumming helped me learn to speak up for myself. Now I am a member of the Board of Directors at M’Wikwedong and I am an advocate for other youth in my area. This video was created through a research project entitled: Promoting healthy urban environments for young Indigenous peoples: The case of M'Wikwedong Native Cultural Resource Centre. The research team was formed by the M’Wikwedong Youth Group (Ryerson King, Kaitrina Harrisson, Steven Schlonies, Nikita Jones, and James Schlonies) and the Centre for Environmental Health Equity at Queen’s University (Carlos Sanchez-Pimienta and Jeffrey Masuda). This video displays a previous iteration of the name of this project. M'Wikwedong recently changed its name to "M'Wikwedong Indigenous Friendship Centre."